JATIDIRI ORANG MADURA (vis a vis) INDUSTRIALISASI - Ainurrahman Hidayat Ainurrahman Hidayat (Institut Agama Islam Negeri Madura)
Abstrac From the perspective of industrialization policy, the characterization of Madurese is comprehended as two different kinds of things. It seems that they diametrichally post in the distinctive area. This comprehension clearly misleads and shallowize the essence of Madura industrialization. This article is to find a holisctic understanding on Madura industrialization with characterization as an absolut constitutive element. This is also the reflection of the writer using an object formal approach of characterization theory issued by Alfred North Whitehead. The research source of material object has been the entire thought, comprehension, and Madura industrialization meaning from the writer’s perspective. The results indicates that the characterization of Madurese is tightly connected to personality, identity and the uniqueness of Madurese in interacting with the environment— religious values, hard-wroker, life survivor, and straight forwarder. The strategical plan must be established on the basis of those characterizations. To seperate diametrichally that characterization with the policy of industrialization is truly marginalized the Madurese. Otherwise, it could be inferred a genocide process against Madurese characterization done gradually from the extreme perspective. Kata-kata kunci identity/characterization, Madura-industrialization, marginalization